Professor Paweł Piotrowski – an extraordinary personality in the realm of memoirs (Journal of Face Aesthetics, 2023)
The article presents the biography, numerous achievements and personality characteristics of Professor Paweł Piotrowski (1948–2021). He was an excellent university lecturer and pedagogue, dedicating his profession to the field of dental prosthetics. He has authored and co-authored 102 full-text papers published in scientific journals both in Poland and internationally. Paweł Piotrowski was entrusted with the care of patients after craniofacial tumour operations as an assistant, and he dedicated the rest of his life to this subject. He was the head of the Department of Oral Rehabilitation at PUMS (2004–2015) and additionally in 2007 established the Laboratory of Stomatognathic System Dysfunctions. He was deeply committed to delivering lectures as part of the Postgraduate Course on Facial Aesthetics, as well as conducting numerous courses within various specialisation programs. Moreover, Pawel Piotrowski was characterised by his multifaceted and fascinating personality, and was a unique and exceptional man.
Keywords: Paweł Piotrowski; biography; personal narratives; dentists; dental prosthetics